Definition, management, and training in impacted fetal head at cesarean birth: a national survey of maternity professionals - Katie Cornthwaite; Pauline Hewitt; Jan W. van derScheer; Imogen A. F. Brown; Jenni Burt; Eliane Dufresne; Mary Dixon‐Woods; Tim Draycott; ABC Contributor Group; Thiscovery Authorship Group; Rachna Bahl (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction This study assessed views, understanding and current practices of maternity professionals in relation to impacted fetal head at cesarean birth, with the aim of informing a standardized definition, clinical management approaches and training. Material and methods We conducted a survey consultation including the range of maternity professionals who attend emergency cesarean births in the UK. Thiscovery, an online research and development platform, was used to ask closed‐ended and free‐text questions. Simple descriptive analysis was undertaken for closed‐ended responses, and content analysis for categorization and counting of free‐text responses. Main outcome measures included the count and percentage of participants selecting predefined options on clinical definition, multi‐professional team approach, communication, clinical management and training. Results In total, 419 professionals took part, including 144 midwives, 216 obstetricians and 59 other clinicians (eg anesthetists). We found high levels of agreement on the components of an impacted fetal head definition (79% of obstetricians) and the need for use of a multi‐professional approach to management (95% of all participants). Over 70% of obstetricians deemed nine techniques acceptable for management of impacted fetal head, but some obstetricians also considered potentially unsafe practices appropriate. Access to professional training in management of impacted fetal head was highly variable, with over 80% of midwives reporting no training in vaginal disimpaction. Conclusions These findings demonstrate agreement on the components of a standardized definition for impacted fetal head, and a need and appetite for multi‐professional training. These findings can inform a program of work to improve care, including use of structured management algorithms and simulation‐based multi‐professional training.